1986
DOI: 10.1089/hwm.1986.3.125
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Batch Experiments with Six Polycyclic Aromatic Hydrocarbons and Two Aquifer Materials

Abstract: Batch experiments were carried out to investigate the adsorption of six polycyclic aromatic hydrocarbons (PAH) (naphthalene, fluorene, phenanthrene, anthracene, fluoranthene, and pyrene) by two aquifer materials. The results show that the adsorption of these PAH is adequately described by the linear isotherm model. Adsorption of naphthalene or fluorene in a mixture with other PAH was suppressed slightly compared to measurements when only one compound was in solution. Regression equations relating the slope of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
13
1
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 11 publications
7
13
1
1
Order By: Relevance
“…Karickhoff [3] and Karickhoff et al [15] reported KO, values for NAPH of 1,300 and 870 on surface soils and sediments, respectively. Abdul and Gibson [7] reported that the KO, for NAPH on Borden aqui- The variation of KO, values on aquifer materials found here is greater than observed for surface soils and may be caused by differences in mineralogy or by the degree of organic diagenesis among the samples. Abdul and Gibson [7] reported that the KO, for NAPH on Borden aqui- The variation of KO, values on aquifer materials found here is greater than observed for surface soils and may be caused by differences in mineralogy or by the degree of organic diagenesis among the samples.…”
Section: Discussioncontrasting
confidence: 47%
“…Karickhoff [3] and Karickhoff et al [15] reported KO, values for NAPH of 1,300 and 870 on surface soils and sediments, respectively. Abdul and Gibson [7] reported that the KO, for NAPH on Borden aqui- The variation of KO, values on aquifer materials found here is greater than observed for surface soils and may be caused by differences in mineralogy or by the degree of organic diagenesis among the samples. Abdul and Gibson [7] reported that the KO, for NAPH on Borden aqui- The variation of KO, values on aquifer materials found here is greater than observed for surface soils and may be caused by differences in mineralogy or by the degree of organic diagenesis among the samples.…”
Section: Discussioncontrasting
confidence: 47%
“…Stuart et al [13] and Abdul and Gibson [14] observed the competitive sorption of polycyclic aromatic hydrocarbons in soil. Stuart et al [13] and Abdul and Gibson [14] observed the competitive sorption of polycyclic aromatic hydrocarbons in soil.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid microbial degradation, the soil and the water hoff et al, 1979;Abdul and Gibson, 1986; Weber et al, used for naphthalene solutions were autoclaved for 2 h prior 1992; Pignatello and Xing, 1996), while studies of vapor to each experiment. The autoclaving procedure did not affect the sorption results (not shown).…”
mentioning
confidence: 99%
“…Soil physical properties for L5 and chemical Hydrophobic sorption onto soil organic matter is deproperties for naphthalene are shown in Tables 1 and 2, respecscribed for many chemicals and soil types (e.g., Karicktively. To avoid microbial degradation, the soil and the water hoff et al, 1979;Abdul and Gibson, 1986;Weber et al, used for naphthalene solutions were autoclaved for 2 h prior 1992; Pignatello and Xing, 1996), while studies of vapor to each experiment. The autoclaving procedure did not affect the sorption results (not shown).…”
mentioning
confidence: 99%